PENGINTEGRASIAN CHARACTER BUILDING PADA MATA KULIAH PRONUNCIATION MELALUI PROJECT-BASED LEARNING - Jamilah Jamilah (Jurnal Pendidikan Karakter, 2015)
Abstrak: Penelitian ini bertujuan untuk memperbaiki proses pembelajaran mata kuliah Pronunciationdan untuk mengintegrasikan character building ke dalam mata kuliah tersebut. Project-based learningadalah model pembelajaran yang dipilih untuk mencapai kedua tujuan tersebut, dan proyek yang diambil adalah pertunjukan drama. Perbaikan pembelajaran dilakukan dengan model lesson studyyang diterapkan pada kelas Pronunciation IB yang terdiri dari 20 mahasiswa. Kegiatan ini dilakukanmelalui tiga tahap, yaitu tahap persiapan (plan), tahap pelaksanaan (do) dan tahap evaluasi (see). Datadikumpulkan melalui observasi, dokumentasi, diskusi, dan self assessment. Hasil penelitian menunjukkanbahwa project-based learning adalah model pembelajaran yang tepat untuk mengintegrasikan characterbuilding ke dalam mata kuliah Pronunciation. Dengan project-based learning mahasiswa dapatbelajar dengan gembira, mampu menerapkan kemampuan pronunciation dalam karya nyata, yaitu bermaindrama. Mahasiswa juga memahami orang lain dan bertenggang rasa, bekerja sama dalam tim,bertanggung jawab, menghargai karya orang lain, mengembangkan rasa percaya diri, bersikap kritis,dan terbuka terhadap saran dan pendapat orang lain. Kata Kunci: character building, pronounciation, project based learning  INTEGRATING CHARACTER BUILDING IN PRONUNCIATION COURSE THROUGHPROJECT-BASED LEARNING Abstract: This study is aimed at improving the learning process Pronunciation course  and integratingcharacter building into the course. Project-based learning is a learning model chosen to achieve theseobjectives, and the project taken is drama performance. The learning improvement was achievedthrough lesson study carried out with a model applied to the IB Pronunciation class consisting of 20students. These activities are carried out through three stages, namely the preparatory stage (plan), theimplementation phase (do) and the evaluation phase (see). Data were collected through observation,documentation, discussions, and self-assessment. The results showed that the project-based learningwas a learning model appropriate for integrating character building into the Pronunciation course. Bythe use of project-based learning, the students could learn joyfully and be able to apply the pronunciationability in the real work, in a drama performance. The students also understood others, developedtolerance, worked together in teams, develiped responsibility, respected the work of others,developed self-confidence, was critical as well as open to suggestions and opinions of others. Keywords: character building, pronunciation, project based learning